Gene polymorphisms of tissue plasminogen activator and plasminogen activator inhibitor-1 in Turkish patients with generalized aggressive periodontitis - Gu¨ lnur Emingil (Blackwell Synergy, 2007)
Aim: Tissue plasminogen activator (t-PA) and plasminogen activator inhibitor-1 (PAI-1) have important roles in proteolytic events in periodontitis. The aim of this study was to investigate TPA and PAI-1 gene polymorphisms in relation to susceptibility to generalized aggressive periodontitis (G-AgP). Methods: Genomic DNA was obtained from peripheral blood of 90 G-AgP patients and 154 periodontally healthy subjects. 4G/5G polymorphism in the promoter region of the PAI-1 gene and Alu-repeat insertion/deletion (I/D) polymorphism in intron 8 of the TPA gene were genotyped by polymerase chain reaction and endonuclease digestion. Results: The genotype distributions of TPA and PAI-1 genes were similar between G-AgP and healthy subjects (p>0.05). The distribution of TPA genotypes in G-AgP patients was 33.4% D/D, 44.4% I/D, and 22.2% I/I and was 26.3% D/D, 40.4% I/D, and 33.3% I/I in healthy subjects. The D allele was 55.6% in G-AgP and 46.6% in healthy subjects. There was a significant difference among study groups in D allele frequencies (p50.044). The PAI-1 genotype distribution in G-AgP was 29.1% 4G/4G, 43.0% 4G/5G, and 27.9% 5G/5G, while it was 35.7% 4G/4G, 43.8% 4G/5G, and 20.5% 5G/5G in healthy subjects. Conclusion: These data suggest that the D polymorphic allele of TPA gene polymorphism could be associated with susceptibility to G-AgP in Turkish subjects.